Women in development 01 - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
Women in developmentCTA is to fund a bibliographic project on the role of women in agriculture in southern Africa. The need for such a project was identified during a CTA-sponsored workshop on Agricultural Information Sources in Lilongwe, Malawi...